Teacher Mental Health and Leaves of Absences: A Pilot Study Examining Gender and Care - Ferguson, Kristen; James, Yvonne; Bourgeault, Ivy (Canadian Journal of Education / Revue canadienne de l'éducation, 2022)
The literature reports high levels of occupational stress for teachers, exacerbated by heavy loads of emotional labour in the classroom. We know less, however, about teacher mental health concerns as they relate to leaves of absences and returns to work, and the role gender may play related to leaves of absences and returns to work. Our pilot study aimed to address these gaps using a survey (n= 67) and follow up interviews (n = 8). We found that the stress teachers experienced at school often results from lack of support from administration, increased workload, lack of resources, violence, and isolation, which then impacts home lives. Over a quarter of teachers surveyed have taken a leave of absence from work, with the majority being women. Female teachers often used sick days to care for ill children. Stigma surrounding teacher mental health and leaves of absence were both perceived as prevalent within the profession.